A case of human rabies with a long incubation period in Wuhan. (2021) - Shengli, Meng; Qian, Li; Yan, Sun; Wenjuan, Wu; Jie, Wu; Jinrong, Shi; Zejun, Wang; Xingguo, Li
Highlights: We report one case of human rabies with a long incubation period in Wuhan, China. In Wuhan, many free-roaming dogs are not only dangerous to domestic dogs and livestock, they are also a threat to humans. Epidemiology of rabies with emphasis on its potential to spread in urban-rural fringe in Wuhan has been discussed. The elimination of RABV from free-roaming domestic dogs will drive a considerable reduction in human disease. We showed that the efficient collaboration was important between the hospital and a professional laboratory for rabies diagnosis. Abstract: Rabies remains endemic in China and continues to pose a major threat to public health with a nearly 100 % case fatality rate in humans. We confirmed a case of human rabies in Wuhan, in May 2018. The patient had got a dog bite wound 3 years before symptoms of confusion, hydrophobia, and photophobia onset. On May 14, our laboratory confirmed that the patient was infected with a rabies virus that circulates in dogs in China and died on May 24, two weeks later after admission. Complete glycoprotein gene sequences determined for this isolate indicated the source of a RABV infection was dog-related RABV variants.